2011
DOI: 10.1007/s00345-011-0732-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of urethral vascularity in nulliparous females using high-frequency endovaginal ultrasonography

Abstract: Vascularity differs in different parts of the urethra. Pixel Flux is a valuable tool for providing reproducible quantitative analysis of vascular parameters for the entire urethra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 22 publications
3
25
0
Order By: Relevance
“…These results are comparable to those reported by other authors, [25] although they only reported finding small differences between the two repeated measurements by the same examiner, without specifying the correlation coefficient values or inter-observer reproducibility.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are comparable to those reported by other authors, [25] although they only reported finding small differences between the two repeated measurements by the same examiner, without specifying the correlation coefficient values or inter-observer reproducibility.…”
Section: Discussionsupporting
confidence: 91%
“…Various studies have reported reproducible results in the vascularization of complex structures such as the endometrium and the ovary, with very high intra-and inter-class correlation coefficients. [24] Various investigators have studied female periurethral vascularization, but most employed 2D-US, [25] and published their results on periurethral vascularization using 3D-PDA color histograms, with three vascular indices (VI, FI and VFI). However, the big difference with our study is that they took as the periurethral area a threshold of 5 mm instead of 3 mm which we used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of the results from experiment II b the t-Student test for dependent samples was used. Normal distribution of data was confirmed using the K-S test (Kolmogorov-Smirnov test) (Wieczorek et al, 2011). For evaluation of the results from experiment III the paired t-Student test was used.…”
Section: Discussionmentioning
confidence: 99%
“…To visualize the examined vessel, color coded ultrasonography was used (Gunzel-Apel et al 2001). For the evaluation of the results Pixel Flux ® software (Chameleon Software, Germany) dedicated for dynamic sonographic tissue perfusion measurement was used , Scholbach et al 2004, Wieczorek et. al.…”
Section: Experiments Iibmentioning
confidence: 99%
“…This function could be also very useful for evaluation of perfusion of lymph nodes, especially during such pathological conditions as lymphoma, when the changes in blood flow within the core and cortical areas are present (17). This function could also be used for blood flow evaluation in the wall of the rural organs, such as the uterus or urethra (42).…”
Section: Discussionmentioning
confidence: 99%